Giving the Devil his due satan and cinema - Weinstock, Jeffrey Andrew 1970-; Hansen, Regina M.; Bacon, Simon 1965-; Fowkes, Katherine A.; Hauka, David; Hunter, Russ; Knowlton, Barry C.; Knowlton, Eloise R.; Leeder, Murray; O'Brien, Catherine 1955- (Fordham University Press, 2021)
Cover -- GIVING THE DEVIL HIS DUE -- Title -- Copyright -- Contents -- Introduction: Giving the Devil His Due -- The Sign of the Cross: Georges Méliès and Early Satanic Cinema -- Murnau's Faust and the Weimar Moment -- Disney's Devils -- What's the Deal with the Devil? The Comedic Devil in Four Films -- His Father's Eyes: Rosemary's Baby -- From the Eternal Sea He Rises, Creating Armies on Either Shore: The Antichristology of the Omen Franchise -- The Weird Devil: Lovecraftian Horror in John Carpenter's Prince of Darkness -- Narration and Damnation in Angel Heart -- The Devil's in the Details: Devilish Desire and Roman Polanski's The Ninth Gate -- Agency or Allowance: The Satanic Complications of Female Autonomy in The Witches of Eastwick and The Witch -- "Roaming the Earth": Satan in The Last Temptation of Christ and The Passion of the Christ -- Lucifer, Gabriel, and the Angelic Will in The Prophecy and Constantine -- Advocating for Satan: The Parousia-Inspired Horror Genre -- LIST OF CONTRIBUTORS -- INDEX.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books